Agromorphological and nutritional quality profiles of fluted pumpkin (Telfairia occidentalis Hook F.) as influenced by cultivar, growing medium and soil amendment source - Oyetunde, O.; Benson, G. A. S.; Oyetunde, A. K.; Olalekan, O. J.; Chukwu, C. U.; Anari, K. O. (International Journal of Horticultural Science, 2023)
Fluted pumpkin (Telfairia occidentalis Hook F.) is popular as food and feed around the world. Sixteen treatments were developed from factorial combinations of three factors: cultivar (ugu elu and ugu ala), growing medium (garden soil (GS) and white sand (WS)), and soil amendment source (poultry manure, NPK, supergro and no amendment). A pot experiment was conducted to investigate the agromorphological and nutritional traits of fluted pumpkin obtained from the treatments. Fresh leaves were analyzed for crude protein, crude fibre, crude lipid, total ash, phytate and nitrate concentrations. Data were subjected to analysis of variance and principal component analysis. Mean plots were used to explain the effects of the three factors and profiling was done using the GYT biplot. There were significant (p≤0.05/0.01) mean squares for measured traits, suggesting the possibility of selection among the treatments. Plants in GS consistently out-performed those in WS for shoot weight, leaf length, and number of leaves per plant possibly due to greater availability of nutrients in the GS. Inconsistent patterns observed in the proximate concentrations of pumpkin from the 16 treatments showed the role of interaction among the three factors. Principal component analysis identified some traits as contributors to differences among the treatments which can be basis of selection. Treatments 2, 4, 6, 8, 10, 11, 12, 13, 14, 15, and 16 might be useful to improve vegetative yield while 1, 3, 5, 7, and 9 could improve nutritional values of the fluted pumpkin.